Exploring multi-dimensional recreational quality of beach socio-ecological systems in the Canary Islands (Spain). (February 2018) - Peña-Alonso, Carolina; Ariza, Eduard; Hernández-Calvento, Luis; Pérez-Chacón, Emma
Abstract: Beaches exposed to continuous arrivals of tourists, such as on the Canary Islands, are subject to demands for quality requirements that are more stringent than in other coastal areas with seasonal tourism. It is therefore especially necessary to evaluate the recreational quality of these beaches. This paper develops a system of indicators (accessibility, environmental quality, water quality, comfort, scenic quality, human activity and infrastructure, facilities and safety) which integrates the narratives of stakeholders, and reveals high recreational quality values at urban and semi-urban beaches, moderate to high values at semi-urban beaches, and low values for services at natural beaches. In order to increase the quality of (i) accessibility at urban and semi-urban beaches, (ii) comfort, scenic quality, facilities and safety services at semi-urban beaches and (iii) water quality, facilities and safety at natural beaches, local management practices need to be adapted in accordance with the different types of beaches. Highlights: This research analyzes recreational quality of beaches as socio-ecological system. Proposed index analyzes different dimensions of recreational quality of beaches. Quality is moderate-high in all dimensions (important differences among beach types). Experts and users converge in weighting recreational quality dimensions.